Food Diversification and Dynamic Food Security: Evidence from Poor Households - Dini Yuniarti; Yunastiti Purwaningsih; AM Soesilo; Agustinus Suryantoro (Muhammadiyah University Press, 2022)
An understanding of the determinants of household food security is fundamental for an appropriate food security strategy. Taking the cases in Kulonprogo and Gunung Kidul, Yogyakarta Special Region, we examine the effect of food diversification on the food security of poor households dynamically related to climate change. In addition, we investigate the impact of socioeconomic factors of human capital such as household age, education, household size, income, livestock, land ownership, and dynamic location on food security. There are four categories of dynamics of food security, namely always safe, improving, worse, and always food insecure. We use primary data with longitudinal surveys during El Nino and La Nina. The sample size is 195 households receiving the Family Hope program. To examine the relationship between livelihood assets and food security dynamics, we used Multinomial Logit Regression. The study found that food diversification significantly increases the food security of poor households. Besides that, income, maternal education, livestock, and land ownership can maintain household food security. Therefore, appropriate food security strategies can focus on food diversification programs, education, and financial sector interventions.